Using a vapor-fed anode and saline catholyte to manage ion transport in a proton exchange membrane electrolyzer. Issue 11 (21st October 2021) - Rossi, Ruggero; Hall, Derek M.; Shi, Le; Cross, Nicholas R.; Gorski, Christopher A.; Hickner, Michael A.; Logan, Bruce E.
Abstract : Saline water represents an inexhaustible source of water for hydrogen production from electrolysis. Abstract : Saline water represents an inexhaustible source of water for hydrogen production from electrolysis. However, direct saltwater splitting faces challenges due to chlorine evolution at the anode and the development of Nernst overpotential due to sodium ion transport competition with protons across the membrane. A new approach to minimize chlorine evolution and improve performance is proposed here by using a humidified gas stream (no liquid electrolyte) for the anode and a liquid saltwater catholyte. Charge repulsion of chloride ions by the proton exchange membrane (PEM) resulted in low chlorine generation, with anodic faradaic efficiencies for oxygen evolution of 100 ± 1% with a synthetic brackish water (50 mM NaCl, 3 g L −1 ) and 96 ± 2% with synthetic seawater (0.5 M NaCl, 30 g L −1 ). The enhanced proton transport by the electric field enabled more efficient pH control across the cell, minimizing sodium ion transport in the absence of a liquid anolyte. The vapor-fed anode configuration showed similar performance to a conventional PEM electrolyzer up to 1 A cm −2 when both anode and cathode were fed with deionized water. Much lower overpotentials could be achieved using the vapor-fed anode compared to a liquid-anolyte due to the reduced sodium ion transport through the membranes, as shown by adding NaClO4 to the electrolytes. This vapor-fed anode configuration allows for direct use of saltwater in conventional electrolyzers without additional water purification at high faradaic efficiencies.